Addressing the deficit in chronic traumatic encephalopathy research in Africa: a call for urgent attention - Abdulbasit Opeyemi Muili; Kehinde Alare; Oluwapelumi Samuel Solagbade; Piel Panther Kuol (Chinese Neurosurgical Journal)
Abstract Chronic traumatic Encephalopathy (CTE) has been linked to an increase in the mortality of contact sport athletes in the USA, most especially in the early 2000s due to limited information on its existence. The lack of understanding of its existence resulted in delayed diagnosis and inadequate treatment of the disease for affected individuals. Africa faces a similar gap as awareness and research on CTE remain limited in the region where active participation in contact sports is rising. If no drastic action is taken to mitigate the gap, the region may face similar health consequences in the future. Various challenges responsible for the gap can be attributed to limited infrastructure, limited funding opportunities, and sociocultural factors. To address these challenges, a multifaceted approach is necessary through increasing funding, integrating CTE education into the medical curriculum, improving infrastructure, and resolving sociocultural myths about organ donation.